IMPLEMENTASI PEMBELAJARAN FIQIH BERBASIS KARAKTER DI MADRASAH TSANAWIYAH BAITUL QUR’AN SAMBAS - Fitiyarsih (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the integration of character values in Fiqh learning at MTS Baitul Qur’an, focusing on the transformation of Islamic law into students' actual behavior. The research employs a qualitative approach with a descriptive-analytical method. Data were collected through direct observation of the teaching-learning process and students' worship patterns, as well as an analysis of behavioral evaluation records to review the consistency between planning and character implementation in the field. The results indicate that character implementation is carried out systemically. Fiqh materials are directly linked to character values, such as amanah (integrity) in muamalah and thaharah (cleanliness) as a reflection of self-discipline. Character reinforcement occurs through strictly monitored worship routines in accordance with school regulations. Assessment is conducted through behavioral tracking and documentation of students' worship practices. In conclusion, Fiqh learning at MTs Baitul Qur’an effectively shapes religious and social character through the synchronization of curriculum planning and consistent behavioral supervision.